Luminescent and Photo-Responsive Gold Nanoparticles for Bio-Applications - Cantelli, Andrea <1988> (Alma Mater Studiorum - Università di Bologna, 2016)
In thesis work it has been given an overview of the most recent advances in the synthesis, characterization and bio-medical application of luminescent Gold nanospecies. It has been shown that the combination of photoactuators and nanostructures results in an apparent reduction of dyes PI QYs, due to the nanomaterials absorbance contribution, also in absence of actual interactions between the two components. It has been proposed a simple approach to take into consideration this contribution and to perform quantitative measurements of dyes PI efficiencies variations in presence of nanoparticles. The PI QY reduction has been found to be qualitatively proportional to the magnitude of the interaction between the dye and the particles measured by NMR. It has been shown that strong interaction between the two components result in significant decreases of the dye PI QY. The photoisomerization effectively determines a change in the repartition of the AB derivative between particle monolayer and solution. This confirms that photoisomerization reaction can probably be exploited for light triggered drug release. These results provided valuable tools and methodologies which improved the state of the art in the quantitative study of light triggered processes in nanoparticles based systems. For the first time it has been proven that GNPs luminescence can be switched on and off thanks to the photoisomerization of an azobenzene derivative covalently bound on the Gold surface. This has been proven to happen thanks to an efficient energy transfer between the trans AB derivative and the GNPs which leads to a sensitized NIR emission whose intensity can be tuned by photoisomerization. These unprecedented results are promising for the development of Gold based light responsive nanoparticles for theranostics. Finally, starting from Au25(Cys)18, it has been successfully developed a complex probe for luminescence based imaging composed by NIR emitting GNCs encapsulated inside mesoporous PEGylated silica NPs.